2017
DOI: 10.1016/j.radcr.2017.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal bleeding from supraduodenal artery with aberrant origin

Abstract: Angiography and endovascular embolization play an important role in controlling acute arterial upper gastrointestinal hemorrhage, particularly when endoscopic intervention fails to do so. In our case, the patient presented with recurrent life-threatening bleed in spite of multiple prior endoscopic interventions and gastroduodenal artery embolization. Our teaching points focus on the role of angiography in acute upper gastrointestinal bleed and when to conduct empiric embolization, while reviewing the supraduod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…We collected pooled data on 1019 patients from 32 separate articles selected according to the inclusion and exclusion criteria. We collected 22 studies focusing on UGIB (total 773 patients), one article focusing on LGIB (total 6 patients) and 9 studies that enrolled patients with both UGIB and LGIB (total 240 patients) (Aina et al 2001 ; Arrayeh et al 2012 ; Boros et al 2021 ; Defreyne et al 2001 ; Dempsey et al 1990 ; Dixon et al 2013 ; Encarnacion et al 1992 ; Feld et al 2010 ; Foley et al 2010 ; Green et al 2005 ; Han et al 2017 ; Heianna et al 2014 ; Holme et al 2006 ; Ichiro et al 2011 ; Kaminskis et al 2017 ; Kaminskis et al 2019 ; Katano et al 2012 ; Kim et al 2009 ; Kobayashi et al 2004 ; Lang et al 1992 ; Lau et al 2019 ; Laursen et al 2014 ; Lee et al 2012 ; Ljungdahl et al 2002 ; Mille et al 2015 ; Morris et al 1986 ; Muhammad et al 2019 ; Padia et al 2009 ; Peynircioğlu et al 2011 ; Poultsides et al 2008 ; Rachapalli and Nagabhushan 2018 ; Rösch et al 1972 ; Schenker et al 2001 ; Schuetz and Jauch 2001 ; Shi et al 2017 ; Sildiroglu et al 2014 ; Song et al 2011 ; Spiliopoulos et al 2018 ; Tandberg et al 2012 ; Tipaldi et al 2018 ; Toyoda et al 1995 ; Warneke et al 2004 ; Yap et al 2013 ; Yata et al 2013 ; Yu et al 2021 ; Zhou et al 2013 ). Five studies analysed indications and technique of preventive TAE.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We collected pooled data on 1019 patients from 32 separate articles selected according to the inclusion and exclusion criteria. We collected 22 studies focusing on UGIB (total 773 patients), one article focusing on LGIB (total 6 patients) and 9 studies that enrolled patients with both UGIB and LGIB (total 240 patients) (Aina et al 2001 ; Arrayeh et al 2012 ; Boros et al 2021 ; Defreyne et al 2001 ; Dempsey et al 1990 ; Dixon et al 2013 ; Encarnacion et al 1992 ; Feld et al 2010 ; Foley et al 2010 ; Green et al 2005 ; Han et al 2017 ; Heianna et al 2014 ; Holme et al 2006 ; Ichiro et al 2011 ; Kaminskis et al 2017 ; Kaminskis et al 2019 ; Katano et al 2012 ; Kim et al 2009 ; Kobayashi et al 2004 ; Lang et al 1992 ; Lau et al 2019 ; Laursen et al 2014 ; Lee et al 2012 ; Ljungdahl et al 2002 ; Mille et al 2015 ; Morris et al 1986 ; Muhammad et al 2019 ; Padia et al 2009 ; Peynircioğlu et al 2011 ; Poultsides et al 2008 ; Rachapalli and Nagabhushan 2018 ; Rösch et al 1972 ; Schenker et al 2001 ; Schuetz and Jauch 2001 ; Shi et al 2017 ; Sildiroglu et al 2014 ; Song et al 2011 ; Spiliopoulos et al 2018 ; Tandberg et al 2012 ; Tipaldi et al 2018 ; Toyoda et al 1995 ; Warneke et al 2004 ; Yap et al 2013 ; Yata et al 2013 ; Yu et al 2021 ; Zhou et al 2013 ). Five studies analysed indications and technique of preventive TAE.…”
Section: Resultsmentioning
confidence: 99%
“…All cases of UGIB and LGIB were compared in terms of technical success and clinical outcome. Technical success rate varied from 62% to 100% (Han et al 2017 ; Heianna et al 2014 ; Ichiro et al 2011 ; Katano et al 2012 ; Kim et al 2009 ; Tandberg et al 2012 ; Tipaldi et al 2018 ), with a mean value of 97.7% comparing the data with Freeman-Turkey transformation for meta-analysis of the dataset (fixed affect); the clinical success rate varied from 51% to 100% (Feld et al 2010 ; Heianna et al 2014 ; Ichiro et al 2011 ; Katano et al 2012 ; Morris et al 1986 ; Sildiroglu et al 2014 ; Tandberg et al 2012 ) with a mean value of 80%. Our analysis based on the comparison of studies found no significant differences in outcomes between UGIBs and LGIBs when comparing technical and clinical success.…”
Section: Resultsmentioning
confidence: 99%
“…The SDA, which was first described by Wilkie in 1911, supplies blood to the proximal duodenum [4]. According to previous studies, the SDA most commonly originates from the GDA (26%-55%), followed by the LHA (9%-20%), CHA or PHA (20%), RGA (8%-13%), and less commonly, the cystic artery or PSPDA [4][5][6][7]. Wilkie stated that SDA appeared to be an end artery in most cases [4].…”
Section: Discussionmentioning
confidence: 99%
“…To prevent these adverse effects, the SDA and RGA are commonly embolized prior to HAIC as long as these arteries branch from the gastroduodenal artery (GDA). Anatomic variations of SDA and RGA are widely known [1][2][3][4][5][6][7][8][9]. It is important for vascular interventional radiologists to recognize these variations.…”
Section: Introductionmentioning
confidence: 99%